MDCM, Inc. (B) : strategic IT portfolio management - Jeffery, Mark, (SAGE Knowledge. Cases., 2006)
The case examines the steps involved in developing a portfolio of IT projects aligned with a company's strategic objectives. Specifically, the case describes a situation where a firm has launched a transformation strategy but has yet to develop a complementary IT strategy. Students must select the optimal portfolio of projects aligned with the strategic objectives and define the global project execution strategy.